1997
DOI: 10.1111/1540-5885.1410035
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Cross‐Functional Cooperation: A Comparison of R&D, Manufacturing, and Marketing Perspectives

Abstract: By breaking down the walls among the R&D, manufacturing, and marketing functions, techniques such as concurrent engineering and quality function deployment can pave the way to more effective new product development (NPD). Recognizing the benefits of such cross‐functional efforts, practitioners and researchers have examined the interrelationships among various groups in the NPD process, paying particularly close attention to the R&D–marketing interface. However, manufacturing also plays an important role in NPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
286
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(296 citation statements)
references
References 44 publications
3
286
0
7
Order By: Relevance
“…Contributing to research on product innovation, our results are noteworthy for two reasons. First, product innovation literature has documented the role of collaboration in new product development processes, and several studies have examined the factors affecting successful collaboration (Dougherty 1992, Jassawalla and Sashittal 1998, Song et al 1997. In this study, we bring a procedural justice perspective into this line of research by examining the linkage between perceived procedural justice in top management decisions and collaborative problem solving among project members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributing to research on product innovation, our results are noteworthy for two reasons. First, product innovation literature has documented the role of collaboration in new product development processes, and several studies have examined the factors affecting successful collaboration (Dougherty 1992, Jassawalla and Sashittal 1998, Song et al 1997. In this study, we bring a procedural justice perspective into this line of research by examining the linkage between perceived procedural justice in top management decisions and collaborative problem solving among project members.…”
Section: Discussionmentioning
confidence: 99%
“…The complexities inherent in new product development processes have prompted researchers to look closely at the interactions among project members as they strive to meet common goals (Brown and Eisenhardt 1995, Dougherty 1992, Song et al 1997. Various concepts characterize problem-solving approaches to accomplishing specific tasks such as cooperation (Pinto et al 1993), coordination (Argote 1982), interdependence (Stewart and Barrick 2000), integration (Kahn 1996), and collaboration (Liedtka 1996).…”
Section: Perceived Procedural Justice In Top Management Decisions Regmentioning
confidence: 99%
“…Both innovation networks and multifunctional working, however, also feature significantly in other debates about organisational and industrial flexibility and moves towards leaner and more flexible production systems (e.g. Womack et al, 1991;Levine, 1995;Finegold and Wagner, 1998;Song et al, 1997). Freeman (1991, p. 501), for example, comments "... both empirical and theoretical research has long since demonstrated the importance for successful innovation of both external and internal networks of information and collaboration".…”
Section: Institutional and Contextual Frameworkmentioning
confidence: 99%
“…Rosenberg, 1982;Song et al, 1997) and their adoption is a key feature of lean production (e.g. Levine, 1995;Finegold and Wagner, 1998).…”
Section: Multifunctional Groupsmentioning
confidence: 99%
“…Research shows that building bridges between functions and to suppliers and customers increases the likelihood of success for the company. These bridges can take the form of cross-functional teams with R&D/manufacturing/marketing integration (Song, Montoya-Weiss and Schmidt, 1997), strategic partnerships (Magrath and Hardy, 1994), which can be with both suppliers (Swink and Mabert, 2000) and customers (Campbell and Cooper, 1999). It is stated that collaboration can speed up the technological progress within the company, but it requires an increasing amount of resources to fully handle and control the product development process (Sobrero and Roberts, 2002).…”
Section: Introductionmentioning
confidence: 99%